Adubação nitrogenada em cobertura, no cultivo do milho consorciado em forrageiras com aplicação de fosfato natural em plantio direto - Paulo Cezar Gomes de Assuncao (2024)
The intercropping of forage crops with maize has shown good results and has contributed to reducing nitrogen fertilization over the years. In this regard, this study aims to investigate the productive components and yield in maize cultivation intercropped with brachiarias (Urochloa ruziziensis, Urochloa brizantha cv. Piatã) and Stylosanthes cv. campo grande, in response to N doses in areas with and without natural phosphite application. The experimental design was a randomized block in a 6x4 factorial scheme in split plots, with three replications. In the first factor plots, the following treatments were established: sole maize (M); maize + Urochloa ruziziensis (MR); maize + Urochloa brizantha cv. Piatã (MP); maize + Stylosanthes cv. campo grande (MS); maize + Urochloa brizantha cv. Piatã + Stylosanthes cv. campo grande (MPS); and maize + Urochloa ruziziensis + Stylosanthes cv. campo grande (MRS). In the subplots, the second factor was composed of nitrogen doses in topdressing: 0, 60, 120, and 240 kg ha⁻¹ of N. The M and MPS intercropping treatments resulted in higher grain yield with phosphite application at a nitrogen dose of 240 kg ha⁻¹, while the MRS intercropping achieved the highest grain yield at the dose 237 kg ha⁻¹ of N. The MPS intercropping provided the highest grain yield without phosphite application at the dose 240 kg ha⁻¹ of N, whereas the MP intercropping showed the highest grain yield at the dose 79 kg ha⁻¹ of N. Increasing N doses positively influenced plant height, ear insertion height, and stem diameter up to the dose 130 kg ha⁻¹ of N in the area without phosphite application, as well as an increase in ear insertion height at the dose 125 kg ha⁻¹ of N with phosphite application. The number of grains per ear, number of rows per ear, and the mass of 100 grains benefited from N doses up to 240 kg ha⁻¹ in the area without phosphite application. To determine the moment of highest leaf reflectance, vegetation indices NDVI (Normalized Difference Vegetation Index), NDRE (Normalized Difference Red Edge Index), SAVI (Soil-Adjusted Vegetation Index), and EVI (Enhanced Vegetation Index) were collected, revealing maximum canopy reflectance only between the doses 100 and 166 kg ha⁻¹ of N in the area with phosphite application and between the doses 83 and 142 kg ha⁻¹ of N in the area without phosphite application. Keywords: Zea mays, Urochloa ruziziensis, Urochloa brizantha, Urea, Stylosanthes cv. campo grande, and natural fertilization